Linking preterm infant gut microbiota to nasograstric enteral feeding tubes: exploring potential interactions and microbial strain transmission - Jara, J.; Alba, C.; Del Campo, R.; Fernández, L.; Sáenz de Pipaón, M.; Rodríguez, J. M.; Orgaz, B. (Frontiers in Pediatrics, 2024)
Introduction: Preterm birth is a growing problem worldwide. Staying at a neonatal intensive care unit (NICU) after birth is critical for the survival of preterm infants whose feeding often requires the use of nasogastric enteral feeding tubes (NEFT). These can be colonized by hospital-associated pathobionts that can access the gut of the preterm infants through this route. Since the gut microbiota is the most impactful factor on maturation of the immune system, any disturbance in this may condition their health.Therefore, the aim of this study is to assess the impact of NEFT-associated microbial communities on the establishment of the gut microbiota in preterm infants.A metataxonomic analysis of fecal and NEFT-related samples obtained during the first 2 weeks of life of preterm infants was performed. The potential sharing of strains isolated from the same set of samples of bacterial species involved in NICU's outbreaks, was assessed by Random Amplification of Polymorphic DNA (RAPD) genotyping.In the samples taken 48 h after birth (NEFT-1 and Me/F1), Staphylococcus spp. was the most abundant genera (62% and 14%, respectively) and it was latter displaced to 5.5% and 0.45%, respectively by Enterobacteriaceae. Significant differences in beta diversity were detected in NEFT and fecal samples taken at day 17 after birth (NEFT-3 and F3) (p = 0.003 and p = 0.024, respectively). Significant positive correlations were found between the most relevant genera detected in NEFT-3 and F3. 28% of the patients shared at least one RAPD-PCR profile in fecal and NEFT samples and 11% of the total profiles were found at least once simultaneously in NEFT and fecal samples from the same patient.The results indicate a parallel bacterial colonization of the gut of preterm neonates and the NEFTs used for feeding, potentially involving strain sharing between these niches. Moreover, the same bacterial RAPD profiles were found in neonates hospitalized in different boxes, suggesting a microbial transference within the NICU environment. This study may assist clinical staff in implementing best practices to mitigate the spread of pathogens that could threaten the health of preterm infants.